Omed-Omedan as a Traditional Cultural Expression: Legal Protection of a Communal Intellectual Property in Indonesia - Dwijayanthi, Putri Triari; Samsithawrati, Putu Aras; Sawitri, Dewa Ayu Dian (Jurnal Magister Hukum Udayana (Udayana Master Law Journal), 2022)
The study was aimed to identify, analyze and elaborate the legal arrangement for communal intellectual property protection in Indonesia, including “omed-omedan”. Further, the study also examined the commercial use mechanism of Traditional Cultural Expression, including “omed-omedan”. This writing was normative legal research using statutory approach and conceptual approach. The study indicates that omed-omedan shall be protected as TCE, hence any commercial use of omed-omedan by major industries and/or foreign investors must obtain a permit and fulfill other obligations including but not limited to the distribution of benefits to customary law community in Banjar Kaja, Sesetan as the custodian.